A Novel Homozygous Frameshift Mutation in CCN6 Causing Progressive Pseudorheumatoid Dysplasia (PPRD) in a Consanguineous Yemeni Family - Nagwa E. A. Gaboon; Asia Parveen; Asia Parveen; Ahmed El Beheiry; Jumana Y. Al-Aama; Jumana Y. Al-Aama; Mosab S. Alsaedi; Naveed Wasif; Naveed Wasif; Naveed Wasif (Frontiers Media S.A., 2019)
Background: Progressive pseudorheumatoid dysplasia (PPRD) inherited in an autosomal recessive fashion, is a disabling disease, characterized by platyspondyly, irregularities of the vertebral bodies, narrowing of the intervertebral discs and intraarticular spaces, widening of the epiphysis-metaphysis, polyarthralgia, multiple joint contractures, and disproportionate short stature. A number of studies have been performed on this deformity in various populations around the globe, including the Arab population. Mutations in CCN6, located on 6q22, are reported to cause this anomaly.Case Presentation: The present study describes the investigation of a consanguineous family of Yemeni origin. Clinical examination of the patient revealed short stature with progressive skeletal abnormalities, stiffness and enlargement of small joints of the hands along with restriction of movements of proximal interphalangeal (PIP) and distal interphalangeal (DIP) joints with weakness and gait disturbance. Sanger sequencing revealed a novel homozygous frameshift deletion mutation (c.746delT; p.Val249Glyfs*10) in CCN6 which may lead to NMD (Nonsense mediated decay). This mutation expands the spectrum of pathogenic variants in CCN6 causing PPRD.